(untitled) (Eurasian Journal of History, Geography and Economics, 2023)
This article provides a brief overview of the law. Law is a system of generally binding social norms established or approved by the state. It includes legal relations and basic rights of the citizen, which are strengthened, guaranteed and protected by the state.